Key Practices Of Information Technology Governance Mechanisms For Public Sector: A Systematic Literature Review - Johan J.C. Tambotoh, Harjanto Prabowo, Sani Muhammad Isa, Bonifasius Wahyu Pudjianto (International Journal of Advanced Science and Technology, 2020)
IT-driven public sector innovation urges public sector to improve their IT Governance (ITG) capabilitythrough ITG mechanisms. The ITG mechanisms of the public sector are critical and important capabilitiesfor decision makers to create public value through IT. In line with the increasing use of IT in the publicsector, there have been increasing interests on ITG aspects in the public sector. However, the ITGmechanism in the public sector is still not well-defined yet in the sense that there are inconsistencies andmisconceptions in determining ITG mechanisms in public organizations. Using systematic literature review(SLR) approach on 41 papers discussing ITG implementation and mechanisms in the public sector, thisresearch found several key practices of ITG mechanisms based on decision-making structure, process orprocedural and relational mechanisms.